Optimization and Process Parameters of CNC End Mill ing For Aluminum Alloy 6082 - K. Siva Kumar; Bathina Sreenivasulu (International Journal of Innovations in Engineering Research and Technology, 2021)
The study aims at optimization of cutting parameters in CNC End milling of Aluminum Alloy 6082. CNC milling is a versatile and most widely used operation in present industry. Sur face quality affects fatigue life of components and influences various mechanical properties and has receive d serious attention for many years. In this work, experiments are conducted to analyze the surface roughnes s using various machining parameters such as Spindle speed, feed rate and depth of cut .